Selected health behaviours of type 2 diabetes patients - Samolińska, Wioletta; Kiczorowska, Bożena; Kowalczuk-Vasilev, Edyta; Klebaniuk, Renata; Jakubczak, Ewelina (Polish Journal of Public Health, 2018)
Introduction. Type 2 diabetes is a chronic disease with an epidemic character. Its prevalence is associated with lifestyle, many environmental factors, and genetic determinants. Implementation of diet therapy is the basis for treatment of the disease. Aim. The aim of the study was to assess health behaviours and differences in these behaviours in type 2 diabetes patients taking their age into consideration. Material and methods. The questionnaire survey was carried out among 120 subjects diagnosed with type 2 diabetes. The original questionnaire comprised questions on selected pro-health behaviours, e.g. prophylactic behaviour or self-monitoring in the disease. The statistical analysis was performed on 111 properly completed surveys. The respondents were divided into three age groups: subjects under 60 (n=24), between 60 and 75 (n=64), and over 75 years old (n=23). Results. Regardless of their age, the patients with type 2 diabetes indicated mainly arteriel hypertension as a coexisting complication. The basic element of patients’ self-monitoring was checking the blood pressure and glycaemia. Half of the patients declared body weight control, however, a majority were characterised by excessive body weight and abdominal fat deposits, irrespective of their age. Walking was the most popular form of physical activity chosen by the respondents. Regardless of their age, the type 2 diabetes patients exhibited similar readiness for self-education related to their disease. Conclusions. The surveyed respondents exhibited similar behaviours undertaken to keep healthy. The increase in the regularity of doctor appointments and in the use of pharmacotherapy was closely related to age of the respondents. The advanced age of the respondents had an impact on the regularity of foot inspection. Respondents over 75 years of age adhered to recommendations on the schedule of food and medicine intake, but used diet therapy less frequently.